2016
DOI: 10.29252/ijal.19.2.33
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Thematic Choices and Thematic Progression Patterns in the Research Articles of Well-established and Emerging Disciplines

Abstract: Several studies have employed the theme-rheme construct to examine the generic profile of research articles (RAs). However, they have mostly focused on the subject matter and nature of disciplines, and other disciplinary characteristics as contextual factors which can impact the genre realization have not been considered in the discourse analysis research. This work, therefore, investigates thematic choices and thematic progression patterns in the RA in relation to the status of disciplines as well-established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
5
10
0
1
Order By: Relevance
“…Meanwhile, DHP and STP share comparable figures with merely 3.3% each. This order of frequency is similar to many studies in the existing body of literature (Babaii et al, 2016;Jalilifar, 2010;Nguyen & Nguyen, 2018;Wei, 2016). However, one notable finding emerging from the analysis is that the frequency of SRP is found in this study much surpasses other studies (Ebrahimi & Khedri, 2012;Jalilifar, 2010;Soleymanzadeh & Gholami, 2014;Wei, 2016).…”
Section: Answer To Research Questionsupporting
confidence: 89%
See 2 more Smart Citations
“…Meanwhile, DHP and STP share comparable figures with merely 3.3% each. This order of frequency is similar to many studies in the existing body of literature (Babaii et al, 2016;Jalilifar, 2010;Nguyen & Nguyen, 2018;Wei, 2016). However, one notable finding emerging from the analysis is that the frequency of SRP is found in this study much surpasses other studies (Ebrahimi & Khedri, 2012;Jalilifar, 2010;Soleymanzadeh & Gholami, 2014;Wei, 2016).…”
Section: Answer To Research Questionsupporting
confidence: 89%
“…This pattern is also noted to be beneficial for the readers in that it provides a clear layout for them to expect and catch what the passage is about (Jalilifar, 2010). STP, similarly, is found to be much less common than the others, with frequencies in essays recorded to range from less than 1% in Wei (2016) to approximately 4% in Babaii et al (2016), Jalilifar (2010), Ebrahimi and Khedri (2011). The reason for such low frequency is that this pattern positions new information in the theme, which does not follow the conventional Given-to-New approach preferred by writers, as highlighted by many studies, for example Yang (2015).…”
Section: Thematic Progression and Text Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…The result of topical Theme as the dominant type of Theme is in line with the results of previous studies committed by Az-Zahro (2017), Babaii et al (2016), Jalilifar et al (2017, Katrini and Farikah (2015), Setiawati (2016), and Undayasari and Saleh (2018). Those previous studies figured out that topical Theme was frequently used by the students instead of textual and interpersonal Theme.…”
supporting
confidence: 91%
“…For instance, Heng and Ebrahimi (2012) found that abstracts in research articles in applied linguistics had a lower proportion of marked themes than research articles in economics. Similarly, Babaii et al (2016) investigated the frequency of marked themes in research articles in mechanical engineering, biomedical engineering, horticulture, and environmental sciences, concluding that marked themes are more frequent in mechanical engineering than in the three other disciplines. One final example comes from a study of research-article introductions (Valipour et al, 2017), where the results indicate that chemistry exhibits a higher proportion of marked themes than does linguistics and software engineering.…”
Section: Previous Research On Thematic Structurementioning
confidence: 99%